Penile strangulation by a plastic bottle neck: a novel technique for non-metallic foreign body removal - Jain, Naman; Gadhire, Minakshi; Aher, Kalyani Dnyaneshwar (International Journal of Research in Medical Sciences, 2025)
Penile strangulation is a rare urological emergency requiring immediate intervention to prevent ischemia, necrosis, and functional loss. We reported a 35-year-old male who presented with penile incarceration caused by a rigid plastic bottle neck. The patient’s unsuccessful self-removal attempts partially fragmented the object. A novel extraction technique using a Gigli saw guided over an artery forceps under local anaesthesia enabled safe removal without significant complications. A multidisciplinary approach involving surgical, urological, and psychiatric evaluation ensured complete recovery. This report highlights a simple, low-cost, and reproducible technique for managing non-metallic penile constricting objects and underscores the importance of early intervention and holistic care in such emergencies.